Comparative Analyisis of Software Cost Estimation Project using Algorithmic Method - Muhammad Indra Zul Aqlani; Nuning Septiana (Engineering Software Requirements, 2018)
Software Cost Estimation has become an important factor to determine the efficiency of software development. There are many model of cost estimation like algorithmic model, top-down, and expert judgement. From all those models, Development in Algorithmic model is higher than the others. In this paper we present a comparative analysis of software cost project using algorithmic methods.